AB1059 Assessing Treatment Durability of Infliximab in the Management of Psoriatic Arthritis and Rheumatoid Arthritis Patients in A Canadian Setting. (10th June 2014) - Kelsall, J.; Jovaisas, A.; Rahman, P.; Sholter, D.; Starr, M.; Bensen, W.G.; Sheriff, M.; Olszynski, W.; Zummer, M.; Faraawi, R.; Chow, A.; Kapur, S.; et al.
Abstract : Background: The efficacy of anti-TNF in the management of psoriatic arthritis (PsA) and rheumatoid arthritis (RA) has been demonstrated in numerous controlled clinical trials. Objectives: The objective of this analysis was to assess in Canadian routine clinical practice the durability of treatment with infliximab (IFX) in PsA and RA and the determinants associated with sustainability of IFX. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with infliximab or golimumab as first biologics or after having been treated with a biologic for less than six months. Patients with PsA or RA treated with IFX who were enrolled between 2002 (2005 for PsA patients) and 2012 were included in this analysis. Dose optimization was defined as an increase in the frequency and/or dosing of IFX. Kaplan Meier (KM) estimates and Cox proportional models were used in the analysis. Results: A total of 92 PsA and 830 RA patients were included in the analysis. Mean (SD) age of the PsA and RA patient cohorts was 48.7 (9.9) and 55.8 (13.4) years, respectively, and mean (SD) duration since diagnosis was 6.8 (9.1) and 10.2 (10.1) years, respectively. Twenty seven (29.3%) PsA patients and 407 (49.0%) RA patients had discontinued treatment. Overall KM-based mean (SE) duration of treatment was 41.4 (3.6) months and 61.3 (2.2) months for PsA and RA patients, respectively. Longer treatment duration was associated with significantly greater improvements in pain (parameter estimate PsA: -0.21, P=0.020; RA: -0.27, P<0.001), patient global (PsA: -0.35, P<0.001; RA: -0.28, P<0.001) and HAQ-DI (PsA: -0.01, P<0.001; RA: -0.01, P<0.001). Significant associations with duration of treatment in PsA patients were observed for disease duration (HR=1.04), previous biologic (HR=2.10), baseline TJC28 (HR=1.10), baseline PASI (HR=0.86) and concomitant use of traditional DMARD(s) (HR=0.16) or NSAID(s) (HR=0.38). For RA patients, IFX dose optimization (HR=0.72) and concomitant use of steroids (HR=1.78) were identified as significant predictors of treatment durability. Conclusions: The results of this observational study have shown a high durability of treatment with IFX for patients with PsA or RA in a real-world setting. Concomitant medication use significantly impacts treatment durability. Furthermore, longer disease duration, higher TJC, less severe skin disease at initiation and previous biologic use in PsA, and absence of IFX dose optimization in RA, may be associated with reduced treatment durability. Disclosure of Interest: J. Kelsall: None declared, A. Jovaisas: None declared, P. Rahman: None declared, D. Sholter: None declared, M. Starr: None declared, W. Bensen: None declared, M. Sheriff: None declared, W. Olszynski: None declared, M. Zummer: None declared, R. Faraawi: None declared, A. Chow: None declared, S. Kapur: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen Inc Canada, S. Otawa Employee of: Janssen Inc Canada, M. Shawi Employee of: Janssen Inc Canada, A. Lehman Employee of: Janssen Inc Canada DOI: 10.1136/annrheumdis-2014-eular.4013